Critical Emancipatory Research Approach to Enhance Performance Among Progressed Learners in Life Sciences - Xolisile, Ndaba; Bekithemba, Dube (Mediterranean Journal of Social Sciences, 2021)
In this theoretical paper, we discuss critical emancipatory research (CER) as an approach to enhance performance among progressed learners in life sciences. Most of the progressed learners perform poorly in life science igniting the need to find alternatives to enhance the performance. We have earthed this paper in CER based on the values such emancipation, transformation and social justice which are pertinent to reinvent better performance in life science. To collect data, we used participatory action research ad used thematic approach to make meaning of the data. The finding of the paper is that progressed learners face various vulnerabilities, which impede their performance, necessitated a need to rethink approached used for teaching and learning. The main argument of the article is that CER has the impetus to change the progressed learners’ attitude, enhances effective communication and collaboration between the progressed learners, parents, teachers and the DBE to improve the academic performance of progressed learners in life sciences. Received: 30 March 2021 / Accepted: 25 May 2021 / Published: 8 July 2021